Consensus Guidelines for Therapeutic Drug Monitoring in Neuropsychopharmacology: Update 2017 - Hiemke, C.; Bergemann, N.; Clement, H. W.; Conca, A.; Deckert, J.; Domschke, K.; Eckermann, G.; Egberts, K.; Gerlach, M.; Greiner, C.; Gründer, G.; Haen, E.; Havemann-Reinecke, U.; Hefner, G.; Helmer, R.; Janssen, G.; Jaquenoud, E.; Laux, G.; Messer, T.; Mössner, R.; Müller, M. J.; Paulzen, M.; Pfuhlmann, B.; Riederer, P.; Saria, A.; Schoppek, B.; Schoretsanitis, G.; Schwarz, M.; Gracia, M. Silva; Stegmann, B.; Steimer, W.; Stingl, J. C.; Uhr, M.; Ulrich, S.; Unterecker, S.; Waschgler, R.; Zernig, G.; Zurek, G.; Baumann, P. (Pharmacopsychiatry, 2018)
Therapeutic drug monitoring (TDM) is the quantification and interpretation of drug concentrations in blood to optimize pharmacotherapy. It considers the interindividual variability of pharmacokinetics and thus enables personalized pharmacotherapy. In psychiatry and neurology, patient populations that may particularly benefit from TDM are children and adolescents, pregnant women, elderly patients, individuals with intellectual disabilities, patients with substance abuse disorders, forensic psychiatric patients or patients with known or suspected pharmacokinetic abnormalities. Non-response at therapeutic doses, uncertain drug adherence, suboptimal tolerability, or pharmacokinetic drug-drug interactions are typical indications for TDM. However, the potential benefits of TDM to optimize pharmacotherapy can only be obtained if the method is adequately integrated in the clinical treatment process. To supply treating physicians and laboratories with valid information on TDM, the TDM task force of the Arbeitsgemeinschaft für Neuropsychopharmakologie und Pharmakopsychiatrie (AGNP) issued their first guidelines for TDM in psychiatry in 2004. After an update in 2011, it was time for the next update. Following the new guidelines holds the potential to improve neuropsychopharmacotherapy, accelerate the recovery of many patients, and reduce health care costs.
Keywords: antidepressant drugs; antiepileptic drugs; antiparkinson drugs; antipsychotic drugs; concentration in blood; consensus guidelines, drug analysis; genotyping; neurologic drugs; pharmacogenetics; pharmacokinetics; phenotyping; plasma concentration; psychiatric drugs; reference range; serum concentration; therapeutic drug monitoring; therapeutic window